Toxicity assessment of reduced graphene oxide and titanium dioxide nanoparticles on growth of microorganisms - Ahmad, Nurul Shahidah (2018)
Increasing use of nanoparticles (NPs) for several purposes including cosmetics, paints, plastics, and textiles led to their released into environment. This scenario raises a concern toward potential of toxic effects. To date, access to the toxicity data for most manufactured NPs are limited. Hence, the aim of this study is to investigate the toxicity of NPs on living microbial culture. Prior to that, a simple and fast technique of microbial cell viability quantification was developed. This technique was used in assessing toxicity effect of microbial culture when they are exposed to NPs. The study was focused on reduced graphene oxide (rGO) and titanium dioxide (TiO2) in anatase and rutile forms. Escherichia coli, Bacillus subtilis, and Candida albican were used as the test models to represent Gram-negative, Gram-positive, and yeast culture, respectively. Three microbial quantification techniques were assessed, which are turbidimetric measurement using spectrophotometer, plate count method to enumerate the colony forming units, and direct microscopic count using trypan blue dye that differentiate between viable and dead cells. The latter technique was found to be ideal for fast, easy, non-destructive, economical method and can be used for on-site measurement on viable cell count and thus was used for the subsequent part of this work. Anatase TiO2 gave the highest toxicity effect among other NPs towards all test models, followed by rGO and rutile TiO2. At 100 μg/mL of anatase exposure for 96 hours of incubation time, it inhibits the growth of E. coli, B. subtilis, and C. albican by 75%, 73%, and 65%, respectively. All microbial cells were inhibited and E. coli was found to be the most sensitive towards NPs. In brief, exposure to NPs not only alter the growth rate (μ) value and cause the loss in cell viability, but it affect the onset and length of growth phases such as shorten the log phase and accelerate the onset of deceleration phase, to name a few. Higher dosage and incubation time of NPs increases their toxicity. Cells were suffered from morphological changes as it was exposed to NPs and this correlates well with the results showing a culture with altered growth phase. NPs did not penetrate into cell membrane, but only deposited at the cell surface.